Characteristics, distribution and diagenetic stages of chert in the La Silla Formation (Lower Ordovician), Argentine Precordillera - Raviolo,Mariana M. (2009)
The late Cambrian - late Tremadocian La Silla Formation is a carbonate unit of the eastern Precordillera in Argentina whose facies indicate a shallow platform environment. Until this moment, there were no studies that referred to the diagenetic evolution of these rocks. The present study involves the characteristics and distribution of the silicification that affects this unit and determines its different diagenetic stages through petrographic (with cathodoluminescence support) and stratigraphic analyses. An early diagenetic chert, in a stage previous to the compactation, was observed. This chert is related to silica-rich seawater in contact with permeable and porous sediments. A later pulse of chert, associated with fracturing, also occurs. The knowledge provided by the characteristics and distribution of chert in these carbonates is significant, especially when considering that the La Silla Formation in San Juan province is the most quarried unit for the elaboration of lime.